Intrahepatic cholestasis of pregnancy and gestational diabetes: Protocol for a scoping review of associations, risk factors, and outcomes. - Karima Abubakr; Clare Kennedy; Shahad Al-Tikriti; Amy C O'Higgins; Ciara Coveney; Mensud Hatunic; Mary F Higgins (PLoS ONE)
Background Intrahepatic cholestasis of pregnancy (IHCP) is a pregnancy-related liver disease associated with adverse pregnancy outcomes, including spontaneous preterm labour, fetal hypoxia, meconium-stained liquor and intrauterine death. In women with IHCP, comorbidities may be associated with a greater risk of stillbirth. Recent studies have suggested that cholestasis of pregnancy may be associated with Gestational Diabetes Mellitus (GDM). Objective This scoping review aims to comprehensively investigate the nature and strength of the association between Intrahepatic Cholestasis of Pregnancy (IHCP) and Gestational Diabetes Mellitus (GDM). The review also seeks to identify common risk factors contributing to the association and explore potential adverse effects associated with the concurrent presence of IHCP and GDM. The findings will inform clinical practice and guide future research initiatives in understanding and managing these pregnancy-related conditions. Methods The scoping review followed the guidelines of Arksey, and O'Malley established in 2005, as well as modifications made to them by Levac et al. in 2010. The PRISMA Scoping review guidance shall be followed in reporting this study. Eight different databases are proposed to search, including Google Scholar, PubMed, Cochrane, Scopus, Embase, CINAHL, the American Diabetes Association, and the Wiley Online Library. Additionally, focused searches within the American Journal of Obstetrics and Gynecology (AJOG) will be conducted, and citation pearl indexing performed.